(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives of the study: To assess the awareness of family members about the disease and how to treat and care for epilepsy patients at home. Subjects and methods: A cross-sectional descriptive study on 43 family members of patients with epilepsy at Nam Dinh Psychiatric Hospital. Results: The patient’s family still lacks a lot of knowledge about the disease such as causes and manifestations of the disease; family members’ knowledge of handling is not high; The number of family members said that adherence to medication and nutritional care and morale was higher with over 60% and 90% respectively. Conclusion: Care and management of patients with epilepsy in the community is a matter of concern, it is necessary to improve knowledge and attitudes for family members and communities in patient care to improve the quality of life for patients with epilepsy.